2021
DOI: 10.3389/fvets.2021.698760
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Study of Cattle Productivity in Intensive Dairy Farms in Central Ethiopia

Abstract: Ethiopia is witnessing an emergence of intensive urban dairy farming. The aims of this study were to capture cattle productivity parameters in selected intensive dairy farms in and around Addis Ababa (Central Ethiopia). The study is a pre-requisite and baseline for further economic analysis of diseases such as bovine tuberculosis (BTB) and to assess some of the current challenges faced by farm owners for optimal animal performances. Hence, a 3-year longitudinal observational study was conducted for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In the crop-livestock mixed and the pastoral systems, offtake of adults was higher than sub adults and juveniles. Tschopp et al ( 19 ) reported that the total offtake rate in the specialized dairy system as 0–71%.…”
Section: Resultsmentioning
confidence: 99%
“…In the crop-livestock mixed and the pastoral systems, offtake of adults was higher than sub adults and juveniles. Tschopp et al ( 19 ) reported that the total offtake rate in the specialized dairy system as 0–71%.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the constraints and data needs ( Table 1 ) had been reported previously by Beyu (2016) , including inadequate animal health services and high drug costs, inadequate quality feed supplies, poor productivity and genetics, and weak development of dairy co-operatives. Tschopp et al . (2021) also recently highlighted the lack of dairy productivity data in Ethiopia.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that animals mated by a Holstein Friesian x Horro sire had a higher conception rate (80.7±2.9%) than animals mated by a pure Jersey sire (78.5±2.4%), a pure Horro sire (74.5±1.8%), a pure Holstein Friesian sire (73.3±2.4%) and a Jersey-Horro sire (67.7±3.8%), respectively. In Addis Ababa, however, the rate of successful conception after arti cial insemination (AI) was 66.1% (Tschopp et al, 2021). CR was higher than Legesse Belay et al(2016), who reported 60.4% in Southern Region of Ethiopia.…”
Section: Calving Interval (Ci) and Days Open (Do)mentioning
confidence: 91%
“…Tadesse et al (2010) revealed that parity and calving season have a signi cant in uence on CI and DO, which is consistent with these ndings. The average CI for intensive dairy farms in Central Ethiopia was 483.2 days (Tschopp et al 2021). Moreover, Mezgebe et al (2018) observed that cows with a shorter calving interval give birth earlier in the calving season, making cows conceive more easily and increasing calves' growth performance.…”
Section: Calving Interval (Ci) and Days Open (Do)mentioning
confidence: 99%